Design and Development of a Press Machine for Biobriquettes Made from Patchouli Distillation Waste and Rice Husk - Vincen Tandiapa; Rifan Pantow; Simon Simanjuntak; Friani Manoppo; Josephine Raphaela; Tineke Saroinsong; Alfred Noufie Mekel; Firmansyah Reskal Motulo; Estrela Bellia Muaja (Asosiasi Dosen Muda Indonesia, 2026)
The increasing availability of biomass residues such as patchouli distillation waste and rice husk presents an opportunity for renewable energy production; however, their utilization remains limited due to the lack of efficient and safe small-scale processing equipment. Developing practical briquette production systems is therefore essential to support sustainable energy use at household and MSME levels. Objective: This study aims to develop and evaluate a hydraulic briquette press capable of producing biomass briquettes from patchouli distillation waste and rice husk while enhancing operational safety, maintenance efficiency, and usability for small-scale production. Method: The research employed an engineering research-and-development approach involving machine design, prototype fabrication, and functional testing. Data were collected through technical observation and performance monitoring of pressing cycles, followed by descriptive analysis to evaluate operational functionality, safety response, and cleaning effectiveness. Findings: The developed press integrates a pressure-sensor-based safety system and an automatic pneumatic cleaning mechanism. The machine is capable of forming six briquettes per cycle at an operating pressure of approximately 50 kg/cm². The integrated systems functioned as intended, supporting stable operation, reducing manual cleaning needs, and improving operational safety. Implications: The proposed design demonstrates potential for improving briquette production efficiency and reliability in small-scale applications. By reducing downtime and enhancing safety, the system can support wider adoption of biomass briquette technology and contribute to community-level renewable energy utilization. Originality/Value: This study offers a novel integration of hydraulic pressing, automatic pneumatic cleaning, and pressure-based safety monitoring within a single multi-cavity briquette press, providing a practical and user-oriented solution for transforming agricultural waste into renewable energy products.